Digital Instructional Leadership Strategies Of School Principals In Strengthening The Quality Of Islamic Education In Elementary Schools - Chaeriansyah, Muhammad Azrial; Sitika, Achmad Junaedi; Rukajat, Ajat (IJGIE (International Journal of Graduate of Islamic Education), 2026)
Digital transformation in Islamic education requires school principals to exercise instructional leadership that combines technological skills with Qur'anic values. To clarify the research context, this study was conducted at Salman Al-Farisy Integrated Islamic Elementary School (SDIT) as an institution that has comprehensively implemented educational digitalization. This study aims to analyze the principal's digital instructional leadership strategies in strengthening the quality of Islamic education in elementary schools. Islam-based terms such as pedagogical tazkiyah and Qur'anic values in this study are operationalized as a process of internalizing digital ethics and manners that are systematically integrated into digital learning. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using Miles and Huberman's interactive model. To clarify the triangulation process, this study compared data from principal interviews, digital classroom observation notes, and platform-based instructional supervision documents. The results of the study show three main strategies: (1) strengthening teacher competence through Islamic value-based digital literacy; (2) optimizing learning technology that integrates Qur'anic content and evidence-based digital instructional supervision; and (3) strengthening digital collaboration between teachers, students, and parents through school communication platforms. These findings expand the theories of Islamic Pedagogical Leadership and Professional Digital Competence by introducing the concept of spiritual digital instructional leadership, which is leadership that places technology as a means of internalizing values and pedagogical tazkiyah. This study confirms that the success of the digitization of Islamic education depends on the principal's ability to create a harmonious integration between technology, pedagogy, and spirituality. As an implication, this study offers recommendations for Islamic schools to develop religious digital literacy and a digital evidence-based instructional supervision system.